Effect of 12-Week Basic Gymnastic Training on Physical Fitness in 6 to 7 YearOld Boys - Savucu, Yüksel; Karataş, Metehan; Eskiyecek, Canan Gülbin; Yücel, A. Serdar; Karadağ, Mustafa (Fırat University, 2018)
Gymnastics requires a wide range of locomotor movements, balance and body control movements, which are crucial for the development of children. In this study, it was aimed to investigate the effect of 12-week basic gymnastic training on physical fitness in 6-7 year-old boys. In the study, pretest-posttest model design was used and the study group was determined random 30 boys in 6-7 year-old participated to the study as an experimental group, which has just begun to be gymnastic in Malatya Youth Services and Sports Provincial Directorate. The researcher applied a 30 minute warm-up program based on gymnastic basic movements as well as gymnastics training for 12 weeks, 3 days in a week. In the study, we investigated that significant difference between physical parameters (age, sports age, Body Mass Index-BMI, height and weight), performance characteristics and recorded values of groups. The data obtained of the study were evaluated using the SPSS 17.0 statistical program. The paired t test was used to determine the relationship between the groups and the independent t test was used for the unrelated sample. In addition, arithmetic mean, frequency and percentage were used and significance level was determined as 0.05. As a result, significant differences were found between the first and last measurements in the experimental group. In the experiment group, it was shown that the warm-up phase of the training session affects the performance of the sportsman positively, especially with the increase in the number of training sessions and the number of movements, especially in the gymnastics sport.

Cimnastik, çocukların gelişimi için oldukça önemli olan geniş bir lokomotor hareket, denge ve vücut kontrol hareketleri gerektirir. Bu çalışmada 6-7 yaş gurubu erkek çocuklarda 12 haftalık temel cimnastik eğitiminin fiziksel uygunluklarına etkisinin araştırılması amaçlanmıştır. Araştırmada öntest-sontest model deseni kullanılmış ve random yoluyla çalışma grubu belirlenmiştir. Malatya Gençlik Hizmetleri ve Spor İl Müdürlüğü tesislerinde cimnastiğe yeni başlayan 6-7 yaş gurubundaki toplam 30 erkek çocuk çalışma grubumuzu oluşturmuştur. Araştırmacı tarafından haftada 3 gün olmak üzere 12 hafta boyunca temel cimnastik eğitimi ve cimnastik temel hareketlerine yönelik 30 dakikalık ısınma programı uygulanmıştır. Çalışmada; cimnastikçilerin fiziksel parametreleri (yaş, spor yaşı, vücut kitle indeksi (VKİ), boy ve kilo), performans özellikleri ve grupların kaydedilen değerleri arasında anlamlı farklılıklar araştırılmıştır. Araştırma sonucunda elde edilen veriler, SPSS 17.0 istatistik programı kullanılarak değerlendirilmiştir. Gruplar arasında ilişkiyi belirlemek için eşleştirilmiş t testi ve ilişkisiz örneklem için bağımsız t testi kullanılmıştır. Ayrıca aritmetik ortalama, frekans ve yüzde kullanılmış, anlamlılık düzeyi ise 0.05 olarak belirlenmiştir. Sonuç olarak deney gurubu ilk ve son ölçümler arasındaki anlamlı farklılıklar bulunmuştur. Deney gurubunda branşa yönelik ısınma evresinin her antrenmanda yapılması ile birlikte özellikle cimnastik sporunda antrenman süresi ve hareket sayısının fazlalığının da etkisiyle birlikte branşa yönelik ısınma evresinin sporcunun performansını olumlu yönde etkilediğini göstermiştir.
6-7 Yaş Gurubu Erkek Çocuklarda 12 Haftalık Temel Cimnastik Eğitiminin Fiziksel Uygunluklarına Etkisi